Marketing channel choice and its determinants among small-scale oil palm fruit farmers in Akwa Ibom State, the southern region of Nigeria - Edet, Glory Emmanul; Akpan, Sunday Brownson; Patrick, Ini-mfon Vincent (Asian Journal of Agriculture and Rural Development, 2024)
The study identified preferred marketing channel choices and determinants among oil palm fruit farmers in the southern region of Nigeria. Three hundred oil palm fruit farmers were randomly selected using the multi-stage random sampling technique. Descriptive statistics and logit regression techniques were employed to analyze the collected data. The socio-economic characteristics revealed that female farmers dominated oil palm fruit production in the region. The majority of the farmers were relatively young, literate, and had moderate household sizes but poor social capital accumulation. The study determined that the major marketing channels preferred by oil palm fruit farmers in the region were middlemen/agent marketing and direct sales in local markets. The empirical result identified oil palm fruit farmers’ education, experience, socialization, dependent ratio, non-farm income, farm income, land size, and access to credit as significant positive determinants of the choice of middlemen/agent marketing channel. Conversely, the researchers identified household size as a significant negative determinant. Moreover, marital status and household size significantly and positively influenced the choice of direct sales in the local market. On the contrary, the oil palm fruit farmers’ education, experience, non-farm income, farm income, farmers’ age, distance to the market, hectare of land, and access to farm credit have a significant negative relationship with the choice of direct sales in the local market. For a better and more efficient choice of marketing channel, oil palm farmers should improve their literacy level and build up social capital.